Innovation in clean coal technologies: Empirical evidence from firm-level patent data - Jürgen Kruse; Heike Wetzel (Institute of Energy Economics at the University of Cologne (EWI), 2016)
This article empirically analyzes supply-side and demand-side factors expected to affect innovation in clean coal technologies. Patent data from 93 national and international patent offices is used to construct new firm-level panel data on 3,648 clean coal innovators over the time period 1978 to 2009. The results indicate that on the supply-side a firm's history in clean coal patenting and overall propensity to patent positively affects clean coal innovation. On the demand-side we find strong evidence that environmental regulation of emissions, that is CO2, NOX and SO2, induces innovation in both efficiency improving combustion and after pollution control technologies.
Keywords: C33; O31; Q40; Q55; 330; clean coal technologies; innovation; patents; technological change